Effects of air movement in a hot air dryer on the drying characteristics of colored potato (Solanum tuberosum L.) using computational fluid dynamics - Park, Hyeon Woo; Yoon, Won Byong (International Journal of Agricultural and Biological Engineering, 2018)
The flow fields of hot air in the dryer for drying colored potatoes of which characteristics are highly sensitive to the temperature were simulated using computational fluid dynamics (CFD) simulation. The local air velocity decreased as the distance from the flow inlet increased. The mass and heat transfer coefficients increased from 0.666×10-2 m/s to 1.711× 10-2 m/s, and 6.555 W/(m2•K) to 16.834 W/(m2•K), respectively, as the air velocity increased from 0.207 m/s to 1.567 m/s at 60°C. The drying simulation model using the heat and mass transfer model made accurate predictions. The thermal properties of colored potato, such as the thermal conductivity and specific heat, decreased significantly from 0.440 W/(m•K) to 0.034 W/(m•K) and 3906.45 J/(kg•K) to 2198.52 J/(kg•K), respectively, as the moisture content decreased from 78% to 5%. With the variable thermal and physical properties, the heat transfer simulation model made accurate predictions of the hot-air drying characteristics for the colored potatoes, and the RMSE values for all cases were (1.85±0.27)°C.Keywords: colored potato, hot air drying, drying characteristics, computational fluid dynamics, thickness, air velocityDOI: 10.25165/j.ijabe.20181101.3293Citation: Park H W, Yoon W B. Effects of air movement in a hot air dryer on the drying characteristics of colored potato (Solanum tuberosum L.) using computational fluid dynamics. Int J Agric & Biol Eng, 2018; 11(1): 232–240.